2011
DOI: 10.1021/ac103334b
|View full text |Cite
|
Sign up to set email alerts
|

Controlled and Oriented Immobilization of Protein by Site-Specific Incorporation of Unnatural Amino Acid

Abstract: Immobilization of proteins in a functionally active form and proper orientation is crucial for effective surface-based analysis of proteins. Here we present a general method for controlled and oriented immobilization of protein by site-specific incorporation of unnatural amino acid and click chemistry. The utility and potential of this method was demonstrated by applying it to the analysis of interaction between a pathogenic protein DrrA of Legionella pneumophila and its binding partner Rab1 of human. Kinetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 30 publications
0
51
0
Order By: Relevance
“…Different from prior immobilization techniques, as demonstrated here, the PRE-CISE system is an entirely covalent immobilization that requires only a single substitution or insertion to facilitate immobilization orientation control (Ewers et al, 2005;Kalia et al, 2007;Lim et al, 2014;Seo et al, 2011;Smith et al, 2005). We have demonstrated that by controlling the immobilization orientation, greater enzyme stability can be realized than nonspecific covalent immobilization, even by 50 and 73%.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Different from prior immobilization techniques, as demonstrated here, the PRE-CISE system is an entirely covalent immobilization that requires only a single substitution or insertion to facilitate immobilization orientation control (Ewers et al, 2005;Kalia et al, 2007;Lim et al, 2014;Seo et al, 2011;Smith et al, 2005). We have demonstrated that by controlling the immobilization orientation, greater enzyme stability can be realized than nonspecific covalent immobilization, even by 50 and 73%.…”
Section: Discussionmentioning
confidence: 88%
“…Other sitespecific immobilization technologies have enabled immobilization at many potential residues, but rely on noncovalent techniques (Kalia et al, 2007;Lim et al, 2014;Seo et al, 2011). To our knowledge, no covalent site-specific immobilization method has been previously demonstrated enabling immobilization at residues throughout the enzyme while only requiring a single substitution or insertion.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is more than one reactive group in BMP2, and this method might suffer from poor site-specificity and heterogeneous products. In addition, non-specific chemical modifications can result in inactivation of proteins or their incorrect orientation 1821 .…”
Section: Introductionmentioning
confidence: 99%
“…We chose Cu(I)-catalyzed azide-alkyne cycloaddition (CuAAC) in this study, since it is a high-yielding and reliable reaction forming a stable triazole linkage between biologically inert azide and terminal alkyne groups [16], and readily compatible with aqueous and mild conditions beneficial for protein bioconjugation [17][19]. CuAAC has been embraced for numerous biomolecular conjugation applications since its discovery in 2002 [20][23].…”
Section: Introductionmentioning
confidence: 99%